Trump and the Coming Revolution in Higher Education Internationalization - Altbach, Philip G.; de Wit, Hans (International Higher Education, 2017)
The advent of the Trump Administration in the US along with Brexit in the UK and other changes in Europe will bring a major set of changes to internationalization. The US and the UK will be seen as less attractive for international students. It is likely that the immigration and visa restrictions will grow. Governmental support for programs such as Fulbright and ERASMUS are likely to be cut back. Perhaps most important, the spirit of internationalization in higher education is likely to change.